The Role of Algorithmic Management and High Performance Work Systems in Enhancing Employee Adaptation to Crisis Situations: A Bibliometric Analysis VOSViewer - Ulfa, Oktafina Noor; Usatnoby, Agusto Makun (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the conceptual development in the human resource management (HRM) literature, focusing on the role of algorithmic management and high performance work systems (HPWS) in enhancing employee adaptation during crisis situations. Using a bibliometric approach based on 50 articles from the Scopus database published between 1998 and 2025, along with visualization analysis using VOSviewer, this study identifies the evolution of key themes in modern HRM. The results indicate a shift from technical focuses such as benchmarking and investment toward more strategic and humanistic issues, including perceived organizational support, employee well-being, and the integration of digital technologies into HRM practices. Furthermore, the study reveals that global collaboration patterns are still dominated by developed countries, with limited participation from developing nations. These findings highlight the importance of interdisciplinary and transnational approaches in designing adaptive, fair, and sustainable work systems to address global challenges.